Evaluasi Kebijakan Full Day School terhadap Eksistensi Madrasah Diniyah - Rois Luthfi (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
Full Day School is a policy issued by the Minister of Education and Culture Muhadjir Efendy with the existence of Permendikbud Number 23 of 2017 concerning School Days. With the issuance of this Permendikbud, the original six-day school has become five days with a provision of eight hours of lessons each day. Originally teaching and learning activities were from morning to noon, with this policy teaching and learning activities became morning to evening. Not a few people responded negatively to this full day school policy. They think that full day school can kill afternoon school / religious school / madrasah diniyah activities. In addition, they also think that this policy will make students less social with the community. And there are many other problems. With the negative response from the community, this policy needs to be evaluated. Namely by asking again how the actual process of implementing full day school is?, are all the facilities in schools adequate?, what about the students whose homes are far from school? What about students who have to recite the Koran in Islamic boarding schools or madrasah diniyah in the afternoon?, and so on. The end result of this evaluation is policy revision or even policy deletion.